2016
DOI: 10.1503/jpn.150058
|View full text |Cite
|
Sign up to set email alerts
|

Male veterans with PTSD exhibit aberrant neural dynamics during working memory processing: an MEG study

Abstract: IntroductionPosttraumatic stress disorder (PTSD) is a psychiatric disorder characterized by re-experiencing, avoidance, negative alterations in mood and cognition, and physiologic arousal symptoms, which may develop subsequent to a traumatic event (e.g., combat).1,2 The lifetime prevalence of PTSD in the United States is roughly 7%-9%; 3,4 however, prevalence rates among recent combat veterans are estimated at 13%-22%. 5,6 Previous studies have demonstrated that patients with PTSD experience deficits in memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 62 publications
8
29
0
Order By: Relevance
“…66 A new study of verbal working memory from our laboratory reached a similar conclusion, as veterans with PTSD exhibited normal responses during both encoding and maintenance operations in left hemispheric language regions, but disturbed responses in right inferior frontal, right supramarginal and superior temporal cortices throughout the majority of encoding and maintenance periods (see Figure 5). 67 As with other studies, these right hemispheric responses correlated with PTSD symptom severity, and we propose that such activity in homologue areas reflects compensatory processing in veterans with PTSD. 67 In a follow-up study, we showed that attention training treatment sharply reduced PTSD symptom severity and largely normalized neural activity in these same brain regions during verbal working memory processing.…”
Section: Post-traumatic Stress Disorder (Ptsd)supporting
confidence: 88%
See 2 more Smart Citations
“…66 A new study of verbal working memory from our laboratory reached a similar conclusion, as veterans with PTSD exhibited normal responses during both encoding and maintenance operations in left hemispheric language regions, but disturbed responses in right inferior frontal, right supramarginal and superior temporal cortices throughout the majority of encoding and maintenance periods (see Figure 5). 67 As with other studies, these right hemispheric responses correlated with PTSD symptom severity, and we propose that such activity in homologue areas reflects compensatory processing in veterans with PTSD. 67 In a follow-up study, we showed that attention training treatment sharply reduced PTSD symptom severity and largely normalized neural activity in these same brain regions during verbal working memory processing.…”
Section: Post-traumatic Stress Disorder (Ptsd)supporting
confidence: 88%
“…67 As with other studies, these right hemispheric responses correlated with PTSD symptom severity, and we propose that such activity in homologue areas reflects compensatory processing in veterans with PTSD. 67 In a follow-up study, we showed that attention training treatment sharply reduced PTSD symptom severity and largely normalized neural activity in these same brain regions during verbal working memory processing. 68 …”
Section: Post-traumatic Stress Disorder (Ptsd)supporting
confidence: 88%
See 1 more Smart Citation
“…This study found aberrant oscillatory alpha activity during WM encoding and maintenance in veterans with PTSD. These significant differences in oscillatory activity were found in the right inferior frontal gyrus (IFG), right supramarginal gyrus (SMG), and right inferior parietal areas (McDermott et al, 2015). In this study, we examined whether these neural abnormalities in WM processing could be ameliorated with attention training treatment by collecting pre- and posttreatment MEG recordings from a group of veterans who participated in a recent clinical trial of attention training for PTSD (Badura-Brack et al, 2015).…”
mentioning
confidence: 99%
“…Briefly, we compared pre- and posttreatment recordings from the veterans with PTSD to a control sample of psychologically healthy combat-exposed veterans who completed the identical WM task during a single MEG session. The pretreatment recordings of the veterans with PTSD and the data from the healthy combat-exposed veterans were both a subset of the data reported in McDermott and colleagues (2015), although that study did not examine treatment effects and included additional controls that had not been exposed to combat or any type of trauma. The current study accounted for combat exposure by using a control group comprised only of combat veterans without PTSD.…”
mentioning
confidence: 99%